The Numerical Solution of Gas Filtration in Hydrodynamic Interconnected Two-Layer Reservoirs - Abdurazakov Abdujabbor; Makhmudova Nasiba; Mirzamakhmudova Nilufar (Genius Journals, 2022)
This article discusses specific problems of gas filtration in two-layer reservoirs. For the solution, the method of lines with a combination of simple factorization is applied. For the numerical solution of the problem, the Maple software system was used
Keywords: Gas filtration; two-layer reservoir; method of lines; permeability